The effect of countries’ health and environmental conditions on restaurant reputation - Fernández-Gámez, Manuel A. (2021)
Corporate reputation enhancement in the restaurant industry has recently been increasingly driven by the central importance of consumer review websites and customers’ greater awareness of sustainable practices regarding health and the environment. In this context, the research question of the present study was if there is a relationship between health and environmental conditions, and restaurants’ corporate reputation on a country level. Trying to answer this question, the present study sought to analyze the e ects of countries’ health and environmental conditions on their restaurants’ corporate reputation, thereby contributing to the existing knowledge about how sustainable environments influence the industry’s competitiveness. The research design included di erent methodological approaches, and was divided into three main phases: restaurant corporation identification, reputation database design, and results. To this end, reputation data from a consumer review website were gathered for a sample of restaurant corporations and establishments connected to the European countries on the Healthiest Country Index.The methods were based on regression analysis. The results indicate that restaurant reputation improves in healthy, sustainable environments, specifically in countries ranked as the healthiest. These findings provide a better understanding of how aspects related to health and environmental sustainability influence corporate reputation.